Memory distortion and attitude change—Two routes to cognitive balance. (13th August 2015) - Berthold, Anne; Blank, Hartmut
Abstract: We report novel research investigating memory distortion as an alternative route to cognitive balance, comparing it with attitude change as a well‐known balancing mechanism. Participants received statements from multiple communicators about a controversial topic (national pride in Study 1 and climate protection in Study 2) and remembered these statements immediately or 1 week later. This resulted in initially balanced or unbalanced combinations of the liking for individual communicators and the communicators' statements and in subsequent balance increases due to liking change or misremembering of statements. The contribution of memory distortion to balance was significant but weaker and less efficient than that of liking change, and the contributions were empirically independent (i.e., uncorrelated and differentially related to third variables—specifically, memory strength and individual cognitive consistency motivation). They also had a different temporal trajectory (liking change fast and memory distortion slow). We discuss theoretical and practical implications.